Kesesuaian Dokumen Perencanaan Pengadaan Tanah Bendungan Karian dengan UU Pengadaan Tanah di Kabupaten Lebak - Febri Yudhanto; Priyo Katon Prasetyo; Sudibyanung Sudibyanung (Widya Bhumi, 2021)
Land Acquisition  Law Article 15 Paragraph (1) of Law Number 2 of 2012 concerning Land Acquisition  for  Development in  the  Public  Interest  regulates  the  Land  Acquisition  Planning Document (DPPT) which at least contains the purpose and objectives of the development plan, conformity with the the spatial plan and National and Regional Development Plans, land layout, land area needed, general description of land status, estimated time of land acquisition, estimated time of construction, estimated land value and budgeting plan. DPPT documents became the basic of Land  Acquisition for location determination and anvancing process. Karian Land Aqcuisition is taken as an case study in this research. Karian Dam whose land acquisition began in 2007, until 2020 land acquisition has not yet been completed. Government regulations Number 37 Year 2010 regulating about dams will also be used as material for evaluations. DPPT Karian Dam was compiled in 2016. The purpose of this study was to evaluate the suitability of the 2016 Karian Dam (DPPT) with 73 Criteria for Land Acquisition and  Government Regulations. This research uses a qualitative research method with a descriptive approach. The results of this study 14 criteria are suitable and 59 criteria are not suitable. With dominant points that are not appropriate, namely: (a) General Description of Land Status, (b) Estimated Time of Land Acquisition, (c) Estimated Time of Development Implementation; (d) Estimated Land Value, (e) Budgeting Plan.Keywords: Land Acquisition, Conformity, Dams, Evaluations. Intisari: Pasal 15 Ayat (1) Undang-Undang Nomor 2 Tahun 2012 tentang Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum mengatur tentang Dokumen Perencanaan Pengadaan Tanah (DPPT) yang paling sedikit memuat maksud dan tujuan rencana pembangunan, kesesuaian dengan RTRW dan Rencana Pembangunan Nasional dan Daerah, letak tanah, luas tanah yang dibutuhkan, gambaran umum status tanah, perkiraan waktu pelaksanaan pengadaan tanah, perkiraan jangka waktu pelaksanaan pembangunan, perkiraan nilai tanah dan rencana penganggaran. DPPT tersebut yang akan menjadi dasar bagi pelaksanaan Penetapan Lokasi dan proses lanjutan pengadaan tanah. Sebagai studi kasus maka diambil pelaksanaan pengadaan tanah Bendungan Karian. Bendungan Karian yang pengadaan tanahnya dimulai dari tahun 2007, sampai dengan tahun 2020 belum dapat diselesaikan pengadaan tanahnya. PP Nomor 37 Tahun 2010 mengatur tentang Bendungan akan digunakan sebagai bahan untuk melakukan evaluasi. DPPT Bendungan Karian disusun pada tahun 2016. Tujuan dari penelitian ini adalah mengevaluasi Kesesuaian DPPT Bendungan Karian Tahun 2016 dengan 73 Kriteria Peraturan Perundang- Undangan Pengadaan Tanah dan PP tentang Bendungan. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan dekriptif. Hasil dari penelitian ini 14 kriteria sesuai dan 59 kriteria tidak sesuai. Dengan poin dominan yang tidak sesuai yaitu: (a) Gambaran Umum Status Tanah, (b) Perkiraan Waktu Pelaksanaan Pengadaan Tanah, (c) Perkiraan Waktu Pelaksanaan Pembangunan; (d) Perkiraan Nilai Tanah, (e) Rencana Penganggaran.Kata Kunci: Pengadaan Tanah, Kesesuaian, Bendungan, Evaluasi.